2016
DOI: 10.1038/micronano.2016.22
|View full text |Cite
|
Sign up to set email alerts
|

Multi-analyte biosensor interface for real-time monitoring of 3D microtissue spheroids in hanging-drop networks

Abstract: Microfluidics is becoming a technology of growing interest for building microphysiological systems with integrated read-out functionalities. Here we present the integration of enzyme-based multi-analyte biosensors into a multi-tissue culture platform for 'body-on-a-chip' applications. The microfluidic platform is based on the technology of hanging-drop networks, which is designed for the formation, cultivation, and analysis of fluidically interconnected organotypic spherical three-dimensional (3D) microtissues… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
145
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 139 publications
(149 citation statements)
references
References 60 publications
1
145
0
1
Order By: Relevance
“…To this end, the recently emerged organ-on-a-chip systems that combine advanced microfluidic technologies and tissue engineering approaches to simulate both the biology and physiology of human organs have been developed (8,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). These miniaturized human organ models have several advantages over conventional models, such as more accurate prediction of human responses and, in particular, multiorgan interactions when different organ modules are assembled in a single fluid circuit (7,31).…”
Section: Significancementioning
confidence: 99%
See 1 more Smart Citation
“…To this end, the recently emerged organ-on-a-chip systems that combine advanced microfluidic technologies and tissue engineering approaches to simulate both the biology and physiology of human organs have been developed (8,(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28)(29)(30). These miniaturized human organ models have several advantages over conventional models, such as more accurate prediction of human responses and, in particular, multiorgan interactions when different organ modules are assembled in a single fluid circuit (7,31).…”
Section: Significancementioning
confidence: 99%
“…For example, prototype microphysiometers have been developed for on-line measurement of glucose and lactate (19,35), oxygen (35), transepithelial electrical resistance (24,36,37), ions (38), extracellular acidification rate (pH), and protein biomarkers (39) in organ-on-a-chip systems (40)(41)(42)(43)(44)(45)(46). However, these sensing units were either built upon a single chip and limited in system-level integration and full automation (19), or were designed for measurements over relatively short periods of time in the range of minutes to hours. In addition, despite that the available commercial sensors are able to monitor a wide range of cellular parameters, such as the Multiparametric BioChip-H (for measuring pH, O 2 , temperature, and electrical signals) by Cellasys, GLU.K.OMETER PRO (for glucose) and LAC PRO (for lactate) by BST, and VisiSens (for 2D visualization of pH, O 2 , or CO 2 distributions) by PreSens, the integration of these sensors with organ-on-a-chip platforms cannot be easily achieved due to their incompatibility with microfluidic systems.…”
Section: Significancementioning
confidence: 99%
“…For the real-time on-chip monitoring of the spheroids, several techniques have been developed including the electrode-based biosensors for oxygen [109], glucose and lactate concentration [110] and also pH and electrical impedance [111] measurements. These monitoring techniques alleviate the need for spheroid retrieval from the chip, which effectively reduces the time and cost.…”
Section: Microfluidic Methods For Spheroid Culturementioning
confidence: 99%
“…Several chip devices have been proposed for detection, such as integrated electrode arrays 72 and microfluidics. 73 Misun et al reported a droplet array device with enzyme-modified electrodes for body-on-a-chip applications (Fig. 10).…”
Section: Droplet Detection Containing 3d Cultured Cellsmentioning
confidence: 99%
“…10). 73 The microfluidic platform is based on hangingdrop networks for cultivation and analysis of 3D cultured cells. The device monitored both lactate and glucose from single human colon cancer microtissues through amperometry.…”
Section: Droplet Detection Containing 3d Cultured Cellsmentioning
confidence: 99%